Introduction of the Problem-based learning methodology in the teaching of Legal Veterinary - Luis Alberto Henríquez Hernández; Octavio Pérez Luzardo; Luis Domínguez Boada; Maira Almeida González; Manuel Zumbado Peña (Universitat Politècnica de València, 2015)
Problem-based learning (PBL) is an educational  strategy  centered  on  the student, who will acquire complex concepts being implemented prior knowledge about a particular discipline. In the field of  Legal  Veterinary,  forensic  expertise is a central part of the knowledge that students must acquire. Since 2010/2011, veterinary students from the University of Las Palmas de Gran Canaria, complete a  forensic  expertise  through  PBL.  The students, separated in two groups of 6-8 subjects, work on a problem from two different points of view: defendant and claimant. During the process, students are tutored and the two positions facing in the classroom to defend their point. At that time, the teacher acts as judge, and the rest of students act as jury. the activity is assessed with 1-3 points. For 5 courses, a total of 275 students have completed the activity, with 50.91% of students obtaining the  highest  qualification.  Students  are satisfied with the activity. We therefore conclude  that  the  PBL  methodology applied to Legal Veterinary is well accepted by the students, who perceive that gives them a significant amount of knowledge autonomously. Group work is stimulating and encourages communication between students.